Cornerstones of quality - Lorenzo, Doreen; Goldman, Donna; Kantola, Rick; Amos, William (California : Kantola Productions [production company] ; Sydney : First Training [distributor])
This is a program about quality. Demonstrate techniques for building a quality-centered organization
Accompanied by 1 instructor's manual and 1 study guide
Copy available in DVD format
Executive producer, Steve Kantola, Rick Kantola
Keywords: Quality control; Management -- Quality control; Total quality management